Research - Category A (ARQUISUR Revista, 2025)
Research Award - Category AThe works submitted to the ARQUISUR Research Award are those that derive from knowledge production processes, handled by teachers and/or students of the Faculties or Schools of Architecture of ARQUISUR as part of their academic activity, regardless of their source of financing, whether existed.Category A contains works produced by researchers in training, carried out individually or in groups, by undergraduate students, teachers or graduates with no more than 5 years since graduating at the time of submitting their work to ARQUISUR Award.
Keywords: Arquisur Awards